PENDIDIKAN MULTIKULTURAL INTERRELIGIUS: UPAYA MENYEMAI PERDAMAIAN DALAM HETEROGENITAS AGAMA PERSPEKTIF INDONESIA - Mahathir Muhammad Iqbal (Sosio-Didaktika: Social Science Education Journal, 2014)
This article was written with the purpose to obtain a picture of interreligious conception of multicultural education as an attempt to create peace in the livelihood of the Indonesian nation that is multicult ural. Conception of multicultural education were developed through in-depth and intensive literature studies. The aut hor emphasizes the idea of multireligious and interreligious education models, not monoreligius, so that each eleme nt in different nations and religious beliefs in this country will show the inclusive character including attitude o f brotherhood, mutual tolerance for differences, respect for differences, and to avoid a culture of violence.